(untitled) (Journal of the College of Basic Education, 2025)
The study included five chapters. The first chapter included the introduction and the importance of the research. The research hypotheses were 1-There are statistically significant differences between the results of the pre-tests and the results of the post-tests between the experimental and control groups in learning some basketball skills. 2-There are statistically significant differences between the results of the post-tests of the experimental group and the control group in learning some basketball skills in favor of the experimental group. The second chapter included theoretical studies (McCarthy model, learning styles according to the McCarthy model), as well as the importance of linking in complex skills, chest handling, and peaceful scoring. The third chapter used the experimental method because it is suitable for the nature of the problem to be solved. The research community and sample were determined in the intentional manner consisting of first-stage students from the College of Physical Education and Sports Sciences, Al-Mustansiriya University for the academic year 2023-2024, numbering (175) male and female students, with (5) sections. The sample was selected in a systematic random manner using the lottery method, where the experimental sample group became 30 and the control group 30. The researchers used skill tests (chest handling after performing the tapping, jumping scoring after performing the tapping) where pre-tests were conducted and the steps of the McCarthy model were applied in four steps, which are: The first stage is reflective observation and includes two steps: (connection and integration), the second stage is crystallization of the concept and includes (visualization and media), and the third stage is active experimentation and includes (Application and expansion) and the fourth stage is the tangible material experiences and includes (development and performance), and these eight great steps are the matter of learning patterns and brain control, and their inclusion within the educational unit in the main final section where the number of units reached five educational units at a rate of one educational unit per week and then the post-tests were conducted, a week and the fourth chapter included the presentation, analysis and discussion of the pre- and post-tests and complex skills and post-tests between the experimental and control group. The fifth chapter included conclusions that the special educational units prepared according to the McCarthy model had a positive impact on the experimental group. Recommendations Emphasis on the use of modern educational design according to educational models including McCarthy in university study variables to learn basketball skills